Are International Portfolio Diversification Opportunities Decreasing? Evidence from Principal Component Analysis - Todorov, Galin K. (International Journal of Economics and Financial Issues, 2017)
I use Principal Component Analysis to create an index of portfolio diversification- a quantifiable measure of diversification opportunities offered to US investors by financial markets abroad. The index is estimated for three market clusters: developed, emerging, and world (emerging and developed combined). During the period under study, the portfolio diversification indices for all three clusters display considerable dynamics. This is suggestive of highly variable benefits from investing abroad. In addition, I find that while the diversification opportunities offered by all three market clusters on average decrease between 1995 and 2014, after 2012 they either level off or begin to increase. Furthermore, my study finds that the homogeneity of international markets as well as their vulnerability to common shocks increase simultaneously, regardless of the type of market. Therefore, international diversification is unlikely to provide protection against global shocks. Finally, I find that the level of diversification opportunities is expected to increase, however, decreases are not unlikely. Keywords: International Portfolio Diversification, Index of Portfolio Diversification, Principal Component Analysis, Developed Markets, Emerging Markets, International Financial Markets JEL Classifications: F01; F30; F36; G1